A heated debate: The future cost-efficiency of climate-neutral heating options under consideration of heterogeneity and uncertainty - Michael Moritz; Berit Hanna Czock; Oliver Ruhnau (Institute of Energy Economics at the University of Cologne (EWI), 2024)
To tackle climate change, residential heating must become climate-neutral. Which technology cost- efficiently achieves this goal is a complex question, given the heterogeneity of buildings and existing infrastructure, as well as uncertainty regarding future energy prices and grid fees. This article aims to disentangle this complexity by comparing the future costs of various decentral and central climate-neutral heating options. Using Germany as a case study, we calculate the future levelized costs of major heating technologies for different building and settlement types and a wide range of assumptions for uncertain parameters like energy prices and infrastructure costs. We find that electric heat pumps are economical most often within the modeled range of inputs, deployed either decentrally in rural areas or centrally with heating grids in more urban areas. Hydrogen boilers can also be cost-efficient, mainly in rural areas and scenarios with low hydrogen prices and grid fees or high electricity grid fees. By contrast, heating with synthetic natural gas seems unlikely to be economical across our broad range of plausible input assumptions.
Additional information: An update of this work is available in EWI Working Paper No 05/24: https://hdl.handle.net/10419/315022; More recent version: https://hdl.handle.net/10419/315022
Keywords: Q40; Q42; Q48; D61; E61; 330; Infrastructure costs; Energy prices; Heat pumps; Hydrogen; Decarbonization; Techno-economic analysis; Levelized costs of heating; Residential heating; Building energy